The Quality of Life in Pregnant Women Conceiving Through in Vitro Fertilization - GLOBEVNIK VELIKONJA, Vislava (Zdr Varst, 2015)
OBJECTIVE: The aim was to determine whether pregnant women conceiving through in vitro fertilization (IVF) differ from those conceiving spontaneously in terms of psychological well-being and the quality of life. METHODS: In a prospective study we included 75 women conceived after IVF and 78 who conceived spontaneously in the same time period (control group). All the women were sent a self-report questionnaire about demographic and reproductive history, health, pregnancy concerns, containing Subjective Quality of Life Scale (QLS), Positive and Negative Affect Schedule (PANAS), the Psychological Well-Being Scale (PWB), Beck Depression Inventory (BDI), and Zung Self-Assessment Anxiety Scale (SAS); obstetric and newborn’s data were obtained from medical records. Response rate was 66.6% in the IVF and 83.3% in control group. RESULTS: The mean women’s age was 33.8 years in the IVF, and 32.5 years in the control group (NS). There were no significant differences between groups on the most of the outcome measures assessing psychological status. IVF mothers were just less satisfied in “friend/acquaintances” (P=0.03), a higher percentage had sexual problems prior to conception (P=0.03); the length of hospitalization during pregnancy was longer (P=0.02), and the preterm delivery rate was higher (P=0.01). Withingroup changes over gestation time indicated that IVF women, not controls, showed an increase in positive affect (P=0.04) and purpose in life (P=0.05). CONCLUSIONS: IVF women are inclined to social isolation. Despite more medical problems during pregnancy, they reported improved positive emotions and purpose in life as the pregnancy progressed.